The role of cryopreservation techniques in manufacturing, transport, and storage of Car-T therapy products - Jandova, M; Stacey, G N; Lanska, M; Gregor, I; Rozsivalova, P; Bekova, L; Duchacova, Z W; Belada, D; Radocha, J; Mericka, P; Fuller, B (Cryo letters, 2023)
Several clinical trials have proved the efficacy and safety of T-cells chimeric antigen receptor (CAR-T cells) in treatment of malignant lymphoma and the first products were registered in the European Union in 2018. The shelf-life of CAR-T cell products in the liquid state is short, so cryopreservation offers a significant benefit for logistics in manufacturing and patient management. Direct shipment of the cryopreserved CAR-T cell therapy products to the clinical department is feasible, nevertheless, intermediate storage in the hospital cryostorage facility gives significant advantage in planning of their administration to patients. Moreover, some manufacturers prefer transport of the starting material cryopreserved at the collection site. The cryopreservation protocol used for starting material by the authors is based on combining dimethyl sulphoxide (DMSO) with hydroxyethyl starch (HES) and slow controlled cooling in cryobags housed in metal cassettes. This achieves the mononuclear cell post-thaw viability of 98.8 ± 0.5 % and recovery of 72.8, ± 10.2 %. Transport of the starting material to the manufactures and return transport of the CAR-T therapy product is performed by authorized courier companies. Intermediate cryostorage of the final CAR-T cell therapy product is performed in a separate dry-storage liquid nitrogen container. On the day of infusion, the cryopreserved products are transported to the clinical department in a dry shipper. On the wards the product is removed from the cassette, inserted into a sterile plastic bag, thawed in a 37 degree C water bath followed by immediate intravenous administration. The authors discuss the adherence of the used technology to good manufacturing practice (GMP) principles and genetic safety assurance rules. Doi: 10.54680/fr23310110112.
Keywords: Cold Temperature; Cryopreservation; Humans; Immunotherapy, Adoptive; lidé; imunoterapie adoptivní; nízká teplota; chimerické antigenní receptory; Receptors, Chimeric Antigen; kryoprezervace